2007
DOI: 10.1128/mcb.00680-07
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila DBT Lacking Protein Kinase Activity Produces Long-Period and Arrhythmic Circadian Behavioral and Molecular Rhythms

Abstract: A mutation (K38R) which specifically eliminates kinase activity was created in the Drosophila melanogaster ckI gene (doubletime [dbt]). In vitro, DBT protein carrying the K38R mutation (DBT K/R ) interacted with Period protein (PER) but lacked kinase activity. In cell culture and in flies, DBT K/R antagonized the phosphorylation and degradation of PER, and it damped the oscillation of PER in vivo. Overexpression of short-period, long-period, or wild-type DBT in flies produced the same circadian periods produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
150
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(166 citation statements)
references
References 64 publications
(145 reference statements)
16
150
0
Order By: Relevance
“…In vitro kinase assays with DBT S , DBT L , or C-terminally truncated forms of DBT: DBT-MYC expression was induced in stably transfected cell lines with CuSO 4 , the cell lysates were immunoprecipitated with anti-MYC antibody, the immunoprecipitates were incubated with PER expressed and purified from bacteria, and radiolabeled substrate was detected and quantified by phosphor-imager analysis of SDS-PAGE (Muskus et al 2007). Aliquots of each reaction were also analyzed by immunoblot analysis with an antibody detecting the C terminus of DBT (Figure 1) or the MYC epitope (Figure 2), and the signal for 32 P incorporation was normalized to the signal for DBT, as previously described (Muskus et al 2007).…”
Section: Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro kinase assays with DBT S , DBT L , or C-terminally truncated forms of DBT: DBT-MYC expression was induced in stably transfected cell lines with CuSO 4 , the cell lysates were immunoprecipitated with anti-MYC antibody, the immunoprecipitates were incubated with PER expressed and purified from bacteria, and radiolabeled substrate was detected and quantified by phosphor-imager analysis of SDS-PAGE (Muskus et al 2007). Aliquots of each reaction were also analyzed by immunoblot analysis with an antibody detecting the C terminus of DBT (Figure 1) or the MYC epitope (Figure 2), and the signal for 32 P incorporation was normalized to the signal for DBT, as previously described (Muskus et al 2007).…”
Section: Expressionmentioning
confidence: 99%
“…It was first shown that PER was rhythmically phosphorylated (Edery et al 1994), and isolation and analysis of the dbt mutants in Drosophila then showed that casein kinase I (CKI) targets PER for phosphorylation and degradation Price et al 1998;Rothenfluh et al 2000a;Suri et al 2000;Muskus et al 2007). Doubletime (DBT) has also been proposed to regulate the nuclear localization (Bao et al 2001;Cyran et al 2005;Nawathean et al 2007) and the repressor capacity of PER (Nawathean and Rosbash 2004;Kim et al 2007;Nawathean et al 2007), as well as the phosphorylation of CLK protein (Kim and Edery 2006;Yu et al 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations